Signaling of Earlier-born Children's Endowments, Intra-household Allocation, and Birth-order Effects - Xu Wei; Yi Zhou; Yimin Zhou (Economic Modelling, 2022)
This paper provides a new explanation for birth-order effects by considering the genetic similarity between siblings. We develop a quantity--quality trade-off model in which parents form their expectations of possible future children's endowments by observing the performance of their existing children. Our model shows that having a talented first child may weaken parents' incentive to have additional children due to the substitution effect. However, it also may encourage a second birth due to the signaling effect. Without assuming that children of a specific birth order have a biological advantage or more parental attention, this model predicts a birth-order gap in parents' human capital investment, the magnitude of which depends on the endowments of the first child and its predictive power as a signal of the potential endowment of a possible second child.